Effect of dynamic cyclic shear on frictional strength weakening of a plane joint. Issue 165 (February 2023) - Zhang, Kai; Liu, Yaoru; Lei, Qinghua; Hou, Shaokang; Yang, Qiang
Abstract: Understanding and predicting the frictional behavior of rock joints subject to dynamic cyclic loading is essential for the seismic safety of many rock engineering problems. In this paper, cyclic shear experiments were conducted based on a shaking table apparatus. A series of cyclic friction tests covering various earthquake-relevant frequencies was conducted on dry planar joints of granitic rock. The friction behavior especially the dynamic evolution of the frictional strength under cyclic loading was investigated, with the influence of loading frequency on the frictional strength weakening and energy dissipation quantified. Based on the experimental results, we propose a phenomenological model characterizing the dynamic frictional behavior of planar granite joints under cyclic loading. This empirical formulation relates the evolution of joint frictional strength to the number of cycles of dynamic loading. As the frequency increases, the frictional strength and dissipated energy density both show a pronounced reduction, while the strength weakening ratio and the critical number of cycles (at which the residual strength is reached) increase in a logarithmic fashion. The frictional strength evolution is described by the product of the peak frictional strength and a damage function, which is further related to the number of cycles and the frequency. In addition, a close inspection of fracture surface morphology after the cyclic loading was conducted to understand the role of surface wear and gouge formation in the frequency-enhanced dynamic friction weakening of rock joints. Highlights: Dynamic cyclic friction tests are conducted on planar granite joints. An empirical model is proposed to describe the frictional behavior of granite. Friction coefficient shows a negative exponential decrease under dynamic cyclic shear. Frictional strength weakening is governed by number of cycles and loading frequencies. Energy dissipation shows a similar evolution behavior as the frictional strength.